Aniline-induced production of aniline-containing polyketides and related bicyclic polyketides by the Yellow River wetland-derived fungus Talaromyces funiculosus - Wang, Zhenhui; Li, Zhanlin; Niu, Chao; Yang, Lanping; Zhai, Yangyang; Li, Dehai; Wu, Guangwei; Zhang, Zhenzhen; He, Xueqian (Frontiers in Microbiology, 2023)
Cultivation of the Yellow River wetland-derived fungus Talaromyces funiculosus HPU-Y01 with aniline led to the isolation of one new aniline-containing polyketide tanicutone A (1), two new bicyclic polyketides tanicutones B-C (2-3), a new related trienoic acid 8-methyldeca-2,4,6-trienoic acid (5) and a known compound 4. The planar structures and configurations of 1-5 were determined by NMR, MS and ECD calculations. Compound 2 featured a key aldehyde group and showed promising inhibitory activity against Vibrio parahaemolyticus with an MIC value of 0.17 μg/mL. This is a rare report of aniline-induced fungal production of tetrahydronaphthone polyketides.